[LB.02.06] APPARENT AND TRUE TREATMENT RESISTANT HYPERTENSION IN GP: A CROSS SECTIONAL STUDY OF PREVALENCE WITH CONSIDERATION OF MORBIDITY, WHITE COAT HYPERTENSION, DOSING AND ADHERENCE. (September 2017) - Hayes, P.; Casey, M.; Glynn, L.; Molloy, G.; Durand, H.; Finn, D.; Newell, J.; Murphy, A.
Abstract : Objective: Treatment Resistant Hypertension (TRH) is defined as high blood pressure in patients taking three or more groups of anti-hypertensive medications (one must be a diuretic) or those taking four or more medications regardless of type and BP level. Target BP levels need to be adapted to specific morbidity (e.g. diabetes), ambulatory blood pressure measurement (ABPM) should be used to exclude white coat hypertension, doses should be the optimal tolerated, and both non-adherence and lifestyle should be examined. Most previous studies have not accounted for these considerations. We conducted a cross sectional study of the prevalence of apparent TRH in general practice, utilizing the appropriate definition, and then considered these issues. Design and method: Forty university-research affiliated practices were invited to participate. We ran a standard ATC drug search identifying patients on any possible hypertensive medications. Two researchers reviewed individual patient's records. The World Health Organisation-Defined Daily Dosing guidelines determined adequate dosing. A measure of adherence was whether patients were printed greater than nine repeat prescriptions within the last year. Results: Sixteen practices participated (N = 50, 878). 2, 807 patients had been prescribed three or more medications previously and of these 646 were deemed to have aTRH. They were largely elderly, male and had co-morbidities (Diabetes 36.7% and Chronic Kidney Disease 40%). 19.0% had adequate medication dosing for each medication and 79.9% were deemed adherent by printed prescription record. Using a BP cut-off of 140/90 mm Hg, the prevalence of aTRH was 6.4% (95%CI 5.8–7.0), 130/80 mm Hg for patients with diabetes or CKD, the prevalence was 10.0% (95%CI 9.3–10.8), reducing to 9.0% (95%CI 8.3–9.7) when a threshold BP of 150/80 mm Hg was applied for over eighties. Considering adequate dosing and adherence reduces prevalence rates even further. Conclusions: Reviewing individual patient records results in a lower estimate of the prevalence of aTRH than has been generally previously reported. Consideration for individual patients of criteria such as morbidity, dosing, white coat hypertension and adherence additionally lowers these estimates, and may be all that is required for the management of the vast majority of cases.